2019
DOI: 10.1007/s11947-019-02393-w
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Non-linear Rheology of Bread Doughs Made from Blends of Wheat (Triticum aestivum L.) and Rye (Secale cereale L.) Flour

Abstract: Strain hardening of wheat flour (WF) proteins during fermentation and baking is at the basis of the excellent quality of wheat breads. Yet, there are good reasons to use rye flour (RF), such as its high content of dietary fiber and other bio-actives. However, rye proteins lack the ability to form dough with sufficient strain hardening capacity under extension, which partially explains the inferior quality of rye breads. A promising strategy to make high-quality breads with high nutritional value is the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Indeed, the SHI could be correlated with bread loaf volume (Table 2). This is in accordance with the conclusions of Meeus et al (2019) and Van Vliet et al (2008) that the strain hardening behaviour of dough during extension is a valuable indicator of bread quality. We showed that this is also the case in a gluten-starch mixture in the presence of wheat bran.…”
Section: 3supporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, the SHI could be correlated with bread loaf volume (Table 2). This is in accordance with the conclusions of Meeus et al (2019) and Van Vliet et al (2008) that the strain hardening behaviour of dough during extension is a valuable indicator of bread quality. We showed that this is also the case in a gluten-starch mixture in the presence of wheat bran.…”
Section: 3supporting
confidence: 93%
“…Strain hardening of gluten proteins in dough promotes equal growth of gas cells and delays their coalescence and disproportionation during late fermentation and early baking (Meeus et al, 2019).…”
mentioning
confidence: 99%
“…Previously it was observed that IWG doughs contain more β-sheets and fewer β-turns when bran is part of the system [ 11 ], which suggests that IWG bran has a dehydrating effect on IWG protein networks as described for wheat dough [ 34 ]. In rye, WE-AX are assumed to contribute to the stability of dough and may form networks that support protein networks [ 35 ]. Currently, little is known about the role of individual flour polymers in establishing networks in IWG dough, but conversion of bran AX by the xylanase used in this study appears to be conducive to dough expansion ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Wheat flour’s balanced gliadin and glutenin profile leads to strain hardening during late proofing and at early baking stages and this makes dough in thinner regions harder to deform than dough in thicker regions [ 35 ], which contributes to uniformly distributed gas cells. The fact that IWG bread appearance suffers from uneven surfaces may be related to a low strain hardening index, which however would need to be assessed in future studies that could also investigate how the parameter is impacted by dough conditioners.…”
Section: Resultsmentioning
confidence: 99%
“…Rye (Chen & Bushuk, 1970) and oat (Peterson, 2016) flour have lower prolamin and glutelin levels than wheat flour (Delcour et al., 2012). Moreover, rye (Meeus et al., 2019) and oat (Hüttner et al., 2010) prolamins and glutelins lack the ability to form a strong viscoelastic protein network that wheat gluten proteins form. As a consequence, hydrating and mixing rye flour results in poorly extensible dough (Verwimp et al., 2006; Weipert, 1997), whereas hydrating and mixing oat flour creates a cake‐like batter (Hüttner et al., 2010; Renzetti et al., 2010).…”
Section: Gas Incorporation and Gas Cell (De)stabilization During Bread Productionmentioning
confidence: 99%